Pembatalan Perkawinan Campuran: Suatu Kajian Yuridis Pertimbangan Hakim - I Putu Ardika Saputra; Andika Natalio; Sandika Dello Primastia; Nobri Novan Harun; Andareksa Andareksa; Anwar Noor Harimurti; Nuraliah Ali (Fakultas Hukum, Universitas Palangka Raya, 2022)
The purpose of this research is to find out and understand the arrangements of mixed marriages in Indonesia in cases of mixed marriage annulment and to know and understand the basis of the judge's legal considerations in the Religious Court Decision Number: 2604 / Pdt.G / 2018 / PA.Jr. This research is normative legal research by referring to the source of legal materials, namely, primary legal materials, secondary legal materials, and tertiary legal materials, and using religious court decision Number: 2604 / Pdt.G / 2018 / PA. Jr) on the annulment of mixed marriages. The results of this study showed that: First, regarding the arrangement of mixed marriages in Indonesia, it needs to be regulated more clearly in Government Regulation of the Republic of Indonesia Number 9 of 1975 concerning the Implementation of Law No. 1 of 1974 concerning marriage jo Law No. 16/2019. Second, in the Religious Court Decision Number: 2604 / Pdt.G / 2018 / PA. Jr. did not look back at whether the conditions that must be met by the respondent in the Regulation of the Minister of Home Affairs Number 12 of 2010 Article 12 paragraph (2) which regulates the conditions for carrying out a mixed marriage that is not fulfilled are intentional by the respondent or not, but only refers to the negligence of the religious affairs office in checking the conditions of marriage that must be fulfilled by the respondent